The persistent competitive advantage of traditional food retailers in Asia: Wet markets' continued dominance in Hong Kong - Goldman, Arieh (Institutional Knowledge at Singapore Management University, 1999)
The focus of this article is the persistent continued strength of wet markets in Hong Kong and the weakness of supermarkets in the fresh food area. This phenomenon is surprising because, based on the experiences in North America and Western Europe and given the well-developed economy of Hong Kong, one would have expected supermarkets to dominate fresh food retailing and wet markets to be in retreat. In this article, the authors explain the reasons for the continued dominance of wet markets. They argue that consumers’shopping and consumption culture, the effectiveness of wet markets in handling consumers’needs, and the appropriateness of the simple technology used by wet markets are at the basis of this dominance. An analysis of developments in the wet market system, in the supermarkets, and in consumers’ behavior leads to a conclusion that there are no indications of possible changes in wet markets’superiority.